Digital marketing effects of Clubhouse on crowdfunding in the context of COVID-19 - Peter Konhäusner; Robert Seidentopf (Journal of Risk and Financial Management, 2021)
In the marketing mix, promotion is mentioned as using the communication channels available to present and market the product or service at hand. In recent years, social media has risen as an influential marketing communication channel in digital space. Apart from end-to-end direct messengers and video communication in times of the COVID-19 pandemic, the social media channel Clubhouse offers an audio-only experience. The current research lacks analysis of the potential influence of the hyped social network. Due to the novelty of the channel and the absence of text messages as well as visual stimuli, questions regarding the impact that usage of this social media channel might have on crowdfunding, a means of rising popularity in alternative financing, have arisen. The study builds upon the media richness theory of Daft and Lengel as well as the channel expansion theory of Carlson and Zmud. Besides literature research, explorative expert interview analyses were applied to answer the research question at hand. The main findings include different approaches to foster the opportunities of Clubhouse for marketing crowdfunding campaigns in line with insights about the user group of Clubhouse as well as development options for the platform.
Keywords: 330; Clubhouse; COVID-19; crowdfunding; marketing; social media; social media marketing